Design and fabricate knee walker for malaysian elderly and disable people - Rosliana, Abdul Jalil (2012)
This thesis is about designing and fabrication of the Knee Walker. The Knee Walker is one of the walking aid for elderly and disable people. The knee walker is a mobility assistance device used by people who have suffered an injury or who are recovering from surgery that has temporarily left them without full use of one of their legs. To achieve the objective of the project, the knee walker must be design for the users that have problem with their injury below the knee that could be Achilles tendon injury, a fracture of foot or ankle and gout problem. The knee walker should be fabricated using welding process and other laboratory process such as drilling process, grinding process and cutting process. This project flow is start from gathered the information, design a concept then fabricated the project. Before the fabricated start all the information are gathered from the source such as internet, book and journal. It is important to know the basic about the knee walker to know about it advantages and disadvantages of the product from other walking aid. The fabrication process must follow step by step to ensure the result fabricated is lightly as the design. The result of fabrication is slightly as the finalized design. From the result obtain also significantly reduce the cost and time to market, and improve product reliability and customer confidence.